Elaboración de una multimedia educativa para ser utilizada como herramienta didáctica y potenciar el aprendizaje del sistema nervioso, en los estudiantes de Noveno Grado de Educación General Básica paralelo “C”, sección matutina del Colegio de bachillerato “Pio Jaramillo Alvarado” de la ciudad de Loja, período 2014 -2015 - Gutierrez Cordova, Neiva Alejandra (2017)
The process of teaching learning oriented in a traditional way or through techniques that are monotonous for students, causes the issues to become boring and very uninteresting; Which is why there is a need to use technology-based teaching techniques known as TIC (Information and Communication Technologies), which allow the use of different resources among which we find educational multimedia where Videos, images and text are used, which make teaching a participative and motivating practice. The present work of titling denominated: ELABORATION OF A EDUCATIONAL MULTIMEDIA TO BE USED AS DIDACTIC TOOL AND POTENTIATE THE LEARNING OF THE NERVOUS SYSTEM, IN THE NINETEENTH DEGREE STUDENTS OF BASIC GENERAL EDUCATION PARALLEL "C", MATCHING SECTION OF THE SCHOOL OF BACHILLERATO "PIO JARAMILLO ALVARADO "OF THE CITY OF LOJA, PERIOD 2014 -2015 aims to employ an educational multimedia as a didactic tool to strengthen the learning about the nervous system in the ninth grade parallel students" C "of the High School" Pio Jaramillo Alvarado " , Canton Loja, Period 2014 - 2015. The research is a longitudinal, qualitative and quantitative study, for which the following methods were taken into account: analytical, synthetic, deductive and inductive, which served to present and contrast the information obtained through bibliographic sources such as books, Web pages, magazines and documents. The bibliographical technique was used for the construction of the theoretical framework, and for the study of the problem the survey was used and as an instrument for collecting the information the questionnaire applied to 30 students of the 9th Year of GBS. Finally, after the analysis of the results and the discussion, it was possible to deduce that the teacher of Natural Sciences of Ninth grade of Basic General Education Parallel "C" of the High School "Pio Jaramillo Alvarado" does not make use of the technological tools which causes Memorable and insignificant learning, for which with results of 0.80 for the first workshop and 0.82 for the second workshop once applied Pearson's correlation coefficient showed that these had a high effectiveness in students, managing to acquire Significant learning in relation to the Nervous System through the application of the proposed multimedia.